Evaluation of a simple technique aiming at optimizing point-by-point isolation of the left pulmonary veins: a randomized study. Issue 8 (5th May 2019) - Kyriakopoulou, Maria; Strisciuglio, Teresa; El Haddad, Milad; De Pooter, Jan; Almorad, Alexandre; Van Beeumen, Katarina; Unger, Philippe; Vandekerckhove, Yves; Tavernier, René; Duytschaever, Mattias; Knecht, Sébastien
Abstract: Aims: We sought to evaluate the efficacy and the safety of a simple technique for stabilizing the ablation catheter during anterior pulmonary vein (PV) encirclement in patients ablated for paroxysmal atrial fibrillation. This consisted of bending the ablation catheter in the left atrium, creating a loop that was cautiously advanced together with the long sheath at the ostium and then within the left superior PV. The curve was then progressively released to reach a stable contact with the anterior part of the left PVs. Methods and results: Eighty consecutive patients (age 64 ± 11 years, left atrial diameter 43 ± 8 mm) undergoing 'CLOSE'-guided PV isolation were prospectively randomized into two groups depending on whether the loop technique was used or not. When using the loop technique, the encirclement of the left PVs was shorter [20 min (interquartile range, IQR 17–24) vs. 26 min (IQR 18–33), P  < 0.01] with a high rate of first pass isolation [(100%) vs. (97%), P  = 0.9] and adenosine proof isolation [(93%) vs. (95%), P  = 0.67]. Most specifically, at the anterior part of the left PVs, there were less dislocations [0 (IQR 0–0) vs. 1 (IQR 0–4), P  < 0.001], radiofrequency duration was shorter (272 ± 85 s vs. 378 ± 122 s, P  < 0.001), force-time integral was higher [524 gs (IQR 427–687) vs. 398 gs (IQR 354–451), P  < 0.001], average contact force was higher [20 g (IQR 13–27) vs. 11g (IQR 9–16), P  < 0.001], and impedance drop was higher [12 Ω (IQR 9–19) vs. 10 Ω (IQR 7–14), P  < 0.001]. Conclusion: This study describes a simple technique to facilitate catheter stability at the anterior part of the left PVs, resulting in more efficient left PV encirclement without compromising safety.